2021
DOI: 10.3390/cancers13092205
|View full text |Cite
|
Sign up to set email alerts
|

Lymph Node Yield and Ratio in Selective and Modified Radical Neck Dissection in Head and Neck Cancer—Impact on Oncological Outcome

Abstract: Background: Lymph node metastases are associated with poor prognosis in head and neck squamous cell carcinoma (HNSCC). Neck dissection (ND) is often performed prior to or after (chemo)radiation (CRT) and is an integral part of HNSCC treatment strategies. The impact of CRT delivered prior to ND on lymph node yield (LNY) and lymph node ratio (LNR) has not been comprehensively investigated. Material and methods: A retrospective cohort study was conducted from January 2014 to 30 June 2019 at the University Hospita… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 46 publications
1
7
1
Order By: Relevance
“…The TLS total area was calculated as the sum of each TLS measured by the manual box selection function of the software Image Pro Plus (Figure 1A ). The minimum p ‐value method was used to further divide TLS+ into two groups, 19 , 20 the TLS low group (TLS L ) and the TLS high group (TLS H ). In our work, the cut‐off values of peritumor and intratumor are 109,941 pixels and 59,440 pixels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…The TLS total area was calculated as the sum of each TLS measured by the manual box selection function of the software Image Pro Plus (Figure 1A ). The minimum p ‐value method was used to further divide TLS+ into two groups, 19 , 20 the TLS low group (TLS L ) and the TLS high group (TLS H ). In our work, the cut‐off values of peritumor and intratumor are 109,941 pixels and 59,440 pixels, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…However, it remains unclear if there is a sex-dependent response difference regarding AT. The prognostic relevance of LNY and LNR has previously been addressed by several studies, 27,28 and the current American Society of Clinical Oncology guidelines state an LNY threshold of 18 as a parameter for an adequate neck dissection. 29 We showed that in the current study's cohort, low LNY was significantly associated with disease recurrence and mortality for patients without AT, while the optimal cutoff was 20 in both cases, independent of the extent of neck dissection, while a higher LNR was significantly associated with mortality, with a cutoff of 4.6% being identified in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopically, (C)RT induces the presence of atypical fibroblasts, swollen endothelial cells, and telangiectasia of thin-walled vessels. These changes manifest macroscopically and radiologically with the presence of tissue edema, fibrosis, and recurrent or chronic tissue inflammation, leading to possible erroneous interpretation of LN pathology [30][31][32] . In a study by our group, Sheppard et al demonstrated a significant reduction of LN yield in NDs of previously irradiated patients [33] .…”
Section: Discussionmentioning
confidence: 99%